Exploring tourist experiences in the lower Kinabatangan River, Sabah: evidence from online reviews - Andi Tamsang Andi Kele; Yuzainy Janin; Arif Kamisan Pusiran; Kamarul Mizal Marzuki; Dayangku Aslinah Abd Rahim; Faerozh Madli (Borneo Tourism Research Centre (BTRC) Universiti Malaysia Sabah, 2022)
Global demand for wildlife tourism is rising and maintaining a positive tourist experience is essential to ensuring the industry's long-term survival. A top location for wildlife tourism, the Lower Kinabatangan River, located in Sabah, Malaysia, is impacted by its surroundings and requires careful management to maintain its reputation for offering pleasant wildlife tourist experiences. This paper aimed to explore tourist experiences in the Lower Kinabatangan River using user-generated content in Web reviews. This paper utilised 186 online reviews extracted from the TripAdvisor website and analysed the data with Leximancer software. Three themes were derived from the data analysis: river, monkey, and trip. The cloud-generated concepts were discussed through the tourist experience's services cape context. The result reveals that most tourist (87.63%) shows positive overall experiences; however, some do show concerns about the issue of rubbishes, dead fish in the river, the invasion of oil palm plantation, and forest destruction. The valuable insights offer a better understanding of the determinants of tourist experiences for the Lower Kinabatangan River to formulate strategies to increase their positive experiences and draw up alternatives to minimise the negative experiences.